Review of the Current Literature and Our Experience on the Value of OCT-angiography in White Dot Syndromes. (17th February 2022) - Mebsout-Pallado, Céline; Orès, Raphaëlle; Terrada, Céline; Dansingani, Kunal K.; Chhablani, Jay; Eller, Andrew W.; Martel, Joseph N.; Anetakis, Alexander; Harwick, Jean C.; Waxman, Evan L.; Gallagher, Denise S.; Prensky, Colin; et al.
ABSTRACT: Purpose: To describe the application of OCT-A in various posterior uveitis disorders in our experience and to compare it with the available literature. Methods: Eighteen eyes with the diagnoses of multifocal choroiditis (MFC), multifocal placoid pigment epitheliopathy (APMPPE), multiple evanescent white dot syndrome (MEWDS), tuberculous serpiginous-like choroiditis (SLC), serpiginous choroiditis (SC), and birdshot chorioretinopathy (BSCR) were studied. Results: We found flow void of the choriocapillaris in patients with APMPPE, SC, MFC, BSCR, and in SLC. In contrast, perfusion of the choriocapillaris seemed normal in patients with MEWDS. Conclusions: We confirmed that OCT-A contributes new information on the physiopathology of white dot syndromes and inflammatory chorioretinopathies, notably on whether or not the choriocapillaris is involved. Comparing the OCT-A features allowed us to suggest that both APMPPE and SLC might be part of the same spectrum of inflammatory disease with primary involvement at the level of the choriocapillaris and secondary RPE damage.